Uso de carne ácida de peito de peru em embutido: impacto da formulação nas características tecnológicas do produto - Kondo, Henry (2014)
With the growing consumption of processed turkey products, knowing the impact of defects caused by the raw material has become very important. Two formulations for production of turkey stuffed product were tested using regular raw meat and other acid turkey meat. For normal acid breast meat was used parameters pH < pH 5.67 and standard meat pH> 5.72 and the remainder of the ingredients and process were identical for both. 30 samples of two slices of cooked turkey built approximately 100g each were vacuum packed and left stored for a period of 40 days at 4 ºC. Then, tests of proximal composition , pH, water retention capacity and dripping were made. No significant differences between the results analyzed samples were detected , showing that the addition of technological ingredients such as soy protein, carrageenan , tapioca starch and phosphate were able to inhibit any defects of use acid meat.